2014
DOI: 10.24059/olj.v19i2.523
|View full text |Cite
|
Sign up to set email alerts
|

Adopting MOOCs on Campus: A Collaborative Effort to Test MOOCs on Campuses of the University System of Maryland

Abstract: To address the paucity of data on the use of MOOCs in "traditional" postsecondary institutions, Ithaka S+R and the University System of Maryland studied the feasibility of repurposing MOOCs for use in hybrid, credit-bearing courses. In this paper we will describe the design of a large-scale study undertaken to examine the use of MOOCs in fourteen campus-based courses, followed by two types of findings: First, we will share quantitative outcomes from students in hybrid sections, comparing students who took MOOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 8 publications
1
29
1
20
Order By: Relevance
“…formative assessment, practical class videos, eBooks, and social media channel). Assessing the impact on students who engaged with the MOOC revealed that a clear majority were in favour, which is generally supported by the literature [33][34][35], but not at the expense of replacing the existing teacher-led sessions. Moreover, the undergraduate students used the MOOC in a personalised manner and engaged with the specific resources which they determined were of benefit to them.…”
Section: Introductionsupporting
confidence: 52%
“…formative assessment, practical class videos, eBooks, and social media channel). Assessing the impact on students who engaged with the MOOC revealed that a clear majority were in favour, which is generally supported by the literature [33][34][35], but not at the expense of replacing the existing teacher-led sessions. Moreover, the undergraduate students used the MOOC in a personalised manner and engaged with the specific resources which they determined were of benefit to them.…”
Section: Introductionsupporting
confidence: 52%
“…To start, some authors have examined the use of MOOCs in campusbased courses and found no statistical difference in pass rate or final score, but the feedback concerning rating, interest, difficulty, and amount learned was better for traditionally taught classes (Griffiths et al, 2015). A pilot was conducted at San José State University (SJSU) with an edX course where a flipped classroom model included projects and quizzes.…”
Section: Blended Learning and Massive Open Online Coursesmentioning
confidence: 99%
“…Literature supports that the above goals are indeed possible to be achieved with MOOCs. For example, one study generated six benefits of incorporating MOOCs in traditionally taught courses: "replaying lectures, augmenting or replacing secondary materials, filling gaps in expertise, exposing students to other styles of teaching and class discussion, reinforcing key skills, and teaching students how to teach online" (Griffiths et al, 2015). Another benefit of embedding MOOCs is that it can help diminish downsides usually reported by researches, such as low completion rate, since high dropout rates in MOOCs can be alarming for traditional educators (Koller, Ng, Do, & Chen, 2013).…”
Section: Blended Learning and Massive Open Online Coursesmentioning
confidence: 99%
See 1 more Smart Citation
“…MOOCs, particularly in the “always open” mode, have the ability to focus students on essential learning they need, conveying the material that is most relevant for the learning objectives of the student. This is sometimes expressed as the “flipped classroom,” where MOOC lectures take the place of classroom lectures, allowing the classroom to be used for other, more personal interactions among and between students and teachers (Griffiths, Chingos, Mulhern, & Spies, ).…”
Section: Areas Of Research From Moocsmentioning
confidence: 99%